PERLINDUNGAN HUKUM KEPADA PEKERJA MIGRAN YANG MENGALAMI KORBAN TINDAK PIDANA PERDAGANGAN ORANG - Firdaus, Muhammad Iqbal; Simangunsong, Frans (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Indonesia is the fourth most populous country in the world, where it is possible that there are many people, whose wealth is not strong enough to find their income through work. Indonesia's goal is to expect the government to produce clear jobs and clear wages. Many citizens want and accept foreign workers. At that time, Indonesia was sending workers abroad. However, it saddened the Indonesian people. Many cases are made by organized human trafficking investigators. However, all this does not cover the fact that many people are attracted to human trafficking by paying a lot of money by working abroad or even in the country. These various regulations are considered an attempt at protectionism by the Indonesian government. Human trafficking is a crime defined under the law. Recognizing the crime of human trafficking, law enforcement is weak, there are human traffickers who try to use the victims as illegal workers in the bad conditions of society